Geology of the boundary between the Sierra Madre Occidental and the Trans-Mexican Volcanic Belt in the Guadalajara region, western Mexico - Andrea Rossotti; Luca Ferrari; Margarita López-Martínez; José Rosas-Elguera (Revista Mexicana de Ciencias Geológicas)
To investigate the time-space relationship between the Sierra Madre Occidental (SMO) and the Trans-Mexican Volcanic Belt (TMVB), as well as the early volcanic activity of the TMVB, a field study was carried out in the region north of Guadalajara City, along the boundary between the two volcanic provinces. Detailed field mapping at 1:50,000 scale, supported by published and new isotopic ages allow to propose a new stratigraphy (30 lithostratigraphic units) and to clarify the volcanic evolution of the region. The SMO succession is made of about 400 m of regional ash flows tuffs of early Miocene age, capped to the south by a basaltic sequence for which we obtained an 40Ar/39Ar age of 21.8 ± 0.3 Ma. The SMO units are sub-horizontal north of García de la Cadena but dip up to 25° to the south of this town, where they are covered in unconformity by the TMVB volcanism.